Critical analysis of the energy performance indicators for road lighting systems in historical towns of central Italy. (1st November 2017) - Leccese, Francesco; Salvadori, Giacomo; Rocca, Michele
Abstract: Energy demand represents a global challenge that calls for innovative energy solutions. Road lighting contributes in a small part to the overall worldwide electricity consumption, however the possibilities for energy saving are numerous. The road lighting should provide the required lighting quality, in the most energy efficient way as possible. In this paper the Authors analyze, compare and discuss the numerical indicators currently used to evaluate the lighting and the energy performance of new-designed and existing road lighting systems. To support the discussion, the use of the case study of road lighting of the historic town center of Pisa is proposed. For the case study the Authors have chosen a significant sample of 20 roads representative of 80 similar roads located in the historic town center. For the sample, geometric surveys, luminance and illuminance measurements, calculation of the national and international energy performance indicators have been carry out. The considerations made by the Authors, obtained with an investigation procedure of general validity, are useful to point out strengths and weaknesses of each indicator and to provide suggestions on the use of the appropriate indicators during the design stage of road lighting systems. Highlights: A review of energy performance indicators for road lighting systems is proposed. Four different indicators, valid at international and Italian levels, are analyzed. To support the discussion, the case study of the public lighting of Pisa is used. To evaluate the indicators a systematic procedure based on in situ measurements is used. Strengths/weaknesses of each indicators and critical issues in their use are highlighted.